2004
DOI: 10.14712/18059694.2018.90
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and β-Carotene Levels During Pregnancy in Gaziantep, Turkey

Abstract: Vitamin A levels during pregnancy have important influences on the health of pregnant women and the growing fetus. Therefore, plasma vitamin A and β-carotene concentrations during pregnancy in Turkish women living in Gaziantep city were investigated in a prevalence study. Optimum sample size was determined as 252 for vitamin A deficiency and vitamin A and β-carotene levels were examined in 427 pregnant women aged 14–44 years. Vitamin A and β-carotene concentrations were measured spectrophotometrically by Neeld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
4
5
0
Order By: Relevance
“…The systolic blood pressure, diastolic blood pressure and mean pressure were significantly raised in subjects with pre-eclampsia compared to normal pregnant and non-pregnant women. But no significant difference was observed between normal pregnant and non-pregnant women which is supported by several studies 2,4,7,12,14 . This study showed increased level of serum copper in pregnancy compared to non-pregnant women which is in agreement with a Turkish study conducted in their population 19 . The physiological importance of these changes remains obscure.…”
Section: Meansupporting
confidence: 92%
“…The systolic blood pressure, diastolic blood pressure and mean pressure were significantly raised in subjects with pre-eclampsia compared to normal pregnant and non-pregnant women. But no significant difference was observed between normal pregnant and non-pregnant women which is supported by several studies 2,4,7,12,14 . This study showed increased level of serum copper in pregnancy compared to non-pregnant women which is in agreement with a Turkish study conducted in their population 19 . The physiological importance of these changes remains obscure.…”
Section: Meansupporting
confidence: 92%
“…Parallel findings were reported in Zimbabwe (31), India (32), and Turkey (33). In the current study, serum retinol significantly declined by about 22% from the first (0.97 µmol/L) to the third trimester (0.76 µmol/L).…”
Section: Discussionsupporting
confidence: 80%
“…This does not necessarily mean that there is a biological reason for the similar Cu levels observed in the aforementioned study populations; it is merely interesting to note that both populations are from African ethnicity. The mean Cu serum concentration of 2451 µg/L in our study is quite similar to that found in a study on pregnant women in Turkey (2206.7 µg/L) [53] but the range in our study (1157 to 4281 µg/L) differs markedly from the range in a study in Spain (936 to 2304 µg/L) [54].…”
Section: Discussionsupporting
confidence: 86%